Prayang Innovation Technology on Capture Results - Huda, Samsul; Naviah, Siti; Habibah, Natasya (Jurnal Perikanan dan Kelautan, 2020)
Prayang is  traditional fishing gear, a prohibition on the use of cantrang fishing gear by the Ministry of Maritime Affairs and Fisheries (KKP) requires an alternative replacement fishing gear, considering that the condition of the Java sea waters is already overfished. The study aims to determine the effect of using different color lights on prayang fishing gear on catches. The research method is an experiment by applying "light fishing" technology. The initial stage of the study was the use of lighting aids with different colors. Based on the results of statistical tests the lamp color treatment had no significant effect, the catch was dominated by white shrimp species for the use of white light and the shrimp continued to prefer green.